The advanced theory of statistics : volume 1 distribution theory - Kendall, Maurice G.; Stuart, Alan. (London : C. Griffin, 1963)
This book is the first volume of a revised version, in three volumes, of Professor Kendall's two-volume work with the same title, the first volume of which appeared in 1943. In this revision he has been joined by his colleague, Mr. Alan Stuart. A good deal of the material in the original Volume 1 has survived and in the earlier chapters the changes are not very extensive. This edition is substantially the same as the first. Minor misprints and errors have been removed, a few improvements have been made in the text, some new exercises have been added and the references brought up to date.
In Three Volumes
Includes index.
Includes bibliographical references: p. 410-418.
aia 26/09/2017
Loans
Keywords: Mathematical statistics